Pemanfaatan Limbah Kulit Buah Menjadi Eco Enzyme Sebagai Alternatif Pengelolaan Sampah Organik Berkelanjutan Di Rt 21, Kelurahan Pagar Dewa, Kec. Selebar, Kota Bengkulu - Bunga Ummu Fadhillah (Yayasan Darussalam Bengkulu, 2026)
Poorly managed household organic waste can cause environmental pollution. One management effort that can be undertaken is processing fruit peel waste into eco-enzymes, a liquid resulting from the fermentation of organic waste that is useful as a natural cleaner, liquid fertilizer, and odor remover. This activity was carried out in RT 21, Pagar Dewa Village, Bengkulu City, with the aim of increasing community knowledge and skills in managing organic waste independently. The methods used included outreach, eco-enzyme production training, mentoring, and evaluation. Eco-enzymes were made with a ratio of 10 parts water, 3 parts fruit peel waste, and 1 part brown sugar or molasses, fermented for 90 days. The results of the activity showed an increase in community understanding regarding organic waste management and the use of eco-enzymes. In addition to reducing the volume of household waste, eco-enzymes also provide environmental and economic benefits. Therefore, utilizing fruit peel waste into eco-enzymes can be a simple and sustainable solution to support community-based waste management.